SIGNIFIKANSI KAJIAN METODOLOGI DALAM PENGEMBANGAN BODY OF KNOWLEDGE EKONOMI ISLAM - Furqoni, Hafas (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2016)
Methodology in science philosophy study is usually discussed in the epistemological discussions which discuss nature, source, concept and theory of knowledge. Methodological discourse, therefore, follows the development of science phylosophy and epistemology discourse. However, there are differences in discussion focus and scope between epistemology and methodology. In epistemology, we study theory of knowledge, its nature and scope, while in methodology we study how to appraise a theory and evaluate it by scientific justification. As a new discipline, methodological discussion in Islamic economics is very important to develop the foundations of the discipline. A solid methodology would help to develop Islamic economics from its own sources of knowledge and use its own philosophical foundations. This paper aims to observe the relationship of Islamic epistemology and methodology of Islamic economics, the nature of Islamic economic methodology and its significance in developing Islamic economics.